Introduction to Evolutionary Genomics - Saitou, Naruya (Computational Biology,, 2013)
Evolutionary genomics is a new discipline that bridges the fields of molecular evolution, bioinformatics and genomics in order to provide a unique perspective on the history of life. This easy-to-follow textbook is the first of its kind to explain the fundamentals of evolutionary genomics. The comprehensive coverage includes concise descriptions of a variety of genome organizations, a thorough discussion of the methods used, and a detailed review of genome sequence processing procedures. The opening chapters also provide the necessary basics for readers unfamiliar with evolutionary studies. Topics and features: Introduces the basics of molecular biology, DNA replication, mutation, phylogeny, neutral evolution, and natural selection Presents a brief evolutionary history of life from the primordial seas to the emergence of modern humans Describes the genomes of prokaryotes, eukaryotes, vertebrates, and humans Reviews methods for genome sequencing, phenotype data collection, homology searches and analysis, and phylogenetic tree and network building Discusses databases of genome sequences and related information, evolutionary distances, and population genomics Provides supplementary material at the website http://www.saitou-naruya-laboratory.org/Evolutionary_Genomics/ This essential text/reference provides an easy-to-read introduction to the field for undergraduate and graduate students, post-doctoral fellows, and established researchers from both computer science and the biological sciences. Dr. Naruya Saitou is a Professor in the Division of Population Genetics at the National Institute of Genetics, and a Professor in the Department of Genetics at the Graduate University for Advanced Studies, Mishima, Japan. He is also a Professor in the Department of Biological Sciences at the University of Tokyo, Japan.